Pilates' : return to life through contrology - Pilates, Joseph H., 1883-1967 (Presentation Dynamics, 1998)
First published in 1945, Pilates? Return to Life Through Contrology contains the authorized, legal, edited, and original Library of Congress version of Joseph H. Pilates and William J. Miller first complete fitness writings. It details the exercises, poses, and instructions fundamental to the matwork developed by Joseph and Clara Pilates. Based on his concepts of a balanced body and mind and drawn from the approach espoused by the early Greeks, these are the exercises that currently sustain a worldwide revolution in fitness strategies and exercise techniques. Readers will learn and view the original 34 exercises that Pilates taught to his students, many of whom have become exercise gurus in their own right. These carefully designed exercises are the result of decades of scientific study, experimentation and research into the variety of physical ills that upset the balance of body and mind. In this book, readers will learn the exercises that Joseph Pilates recommended to accompany his basic advice regarding posture, body mechanics, correct breathing, spinal flexibility, and physical education.